1998
DOI: 10.1016/s0014-5793(98)01609-3
|View full text |Cite
|
Sign up to set email alerts
|

Various glucocorticoids differ in their ability to induce gene expression, apoptosis and to repress NF‐κB‐dependent transcription

Abstract: Glucocorticoids (GCs) influence a great variety of cellular functions by at least three important modes of action: the activation (or repression) of genes controlled by binding sites for the glucocorticoid receptor (GR), the induction of apoptosis in lymphocytes and the recently discovered cross-talk to other transcription factors such as NF-U UB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 25 publications
3
24
1
Order By: Relevance
“…Reasons for the conflicting results are most likely due to the different models being studied and the variation in drug type, dose, and exposure time. It has been shown that synthetic and natural Gc vary in their potency and effects on gene expression and apoptosis (38). Our results differ from many of these studies in that CS, a natural Gc, was administered in vivo to mice continuously for a period of 3 days, with Gc levels that were consistent with natural models of stress.…”
Section: Discussioncontrasting
confidence: 80%
“…Reasons for the conflicting results are most likely due to the different models being studied and the variation in drug type, dose, and exposure time. It has been shown that synthetic and natural Gc vary in their potency and effects on gene expression and apoptosis (38). Our results differ from many of these studies in that CS, a natural Gc, was administered in vivo to mice continuously for a period of 3 days, with Gc levels that were consistent with natural models of stress.…”
Section: Discussioncontrasting
confidence: 80%
“…NF-ĸB [42]. Recent reports have suggested that glucocorticoid-induced apoptosis in lymphocytes is mediated by repressing NF-kB-dependent transcription both in vitro [43]and in vivo [44]. We speculate that the glucocorticoids and nonsteroidal NaSal may have distinct mechanisms for their induction of apoptosis.…”
Section: Discussionmentioning
confidence: 89%
“…In this line, dissociation of glucocorticoid-dependent transactivation and transrepression may lead to the development of better tolerated drugs (20). Already several compounds have been reported to exhibit strong inhibition of NF-B but weak induction of the GRE-dependent reporter gene; however, clinical application of those compounds is still pending (33)(34)(35)(36).…”
mentioning
confidence: 99%